2022
DOI: 10.1002/macp.202200303
|View full text |Cite
|
Sign up to set email alerts
|

Facile Catalyst‐Free Approach toward Fully Biobased Reprocessable Lignin Thermosets

Abstract: Reprocessable and biobased thermosets are prepared from two renewable feedstocks, lignin and polyamine (Priamine 1071). Lignin is oxidized to produce polycarbonyl and further reacts with polyamine to form a crosslinked network of imines. The thermoset materials are formed under heat and pressure in the absence of any catalysts. The mechanical strength and thermal properties of thermosets are tunable by changing feedstock ratios. The dynamic imine crosslinks can be associatively reformed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Furthermore, the decrease in peak intensity for the δ = 100−140 ppm and the formation of a new chemical shift around δ = 60 ppm indicate the conversion of alkenes to thioethers via the thiol-ene reaction. Further studies using 29 Si NMR confirmed the presence of Si in the material at δ = 100 ppm, which corresponds to the chemical shift of the cross-linker (Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Furthermore, the decrease in peak intensity for the δ = 100−140 ppm and the formation of a new chemical shift around δ = 60 ppm indicate the conversion of alkenes to thioethers via the thiol-ene reaction. Further studies using 29 Si NMR confirmed the presence of Si in the material at δ = 100 ppm, which corresponds to the chemical shift of the cross-linker (Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…Since the thiol-ene reaction proceeded via thermal initiation, the thermosets could be used directly for testing after curing. 36 The incorporation of silyl ether crosslinkers into the thermosets was qualitatively measured using FTIR and solid state 13 C and 29 Si NMR (Figure 3 and Figure S6) and ICP-MS (Table S1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, due to the fast kinetics of the exchange reactions taking place in the network, self-healing behavior and fast stress relaxation has been observed in this class of CANs . In addition, the biobased pool of aldehydes is rather extensive, and includes vanillin, syringaldehyde, , furfural, and functionalized lignin. Imine formation is a well-known reaction in which a primary amine reacts with an aldehyde, yielding a CN moiety, with water as the sole byproduct . Taken together, imine-based CANs represent a promising platform as a substituent for nonrenewable materials since dynamic covalent chemistries allow closed-loop recyclability .…”
Section: Introductionmentioning
confidence: 99%